Analysis of Factors Affecting the Decisions of Islamic Stock Investors in Surabaya during the Covid-19 Pandemic - Ibnu Affan; Clarashinta Canggih (Universitas Airlangga, 2022)
ABSTRAK Penelitian ini bertujuan untuk mengetahui faktor-faktor apa saja yang berpengaruh terhadap keputusan investor saham syariah di Surabaya selama pandemi Covid-19. Faktor-faktor tersebut didapatkan melalui market variables, financial literacy, herding behavior, dan risk tolerance. Metode penelitian menggunakan pendekatan kuantitatif dengan teknik analisis yakni analisis faktor konfirmatori. Penelitian ini memakai teknik purposive dan snowball sampling untuk mendapatkan 100 responden melalui kuesioner yang disebar sesuai dengan kriteria yang telah ditentukan. Hasil dari penelitian menyatakan bahwa terdapat tiga faktor yang memengaruhi keputusan investor saham syariah di Surabaya selama pandemi Covid-19 yakni perilaku herding sebagai faktor utama, pengetahuan investasi sebagai faktor kedua, dan market variables sebagai faktor ketiga. Kata Kunci: Perilaku Herding, Pengetahuan Investasi, Market Variables, Keputusan Investasi, Pandemi Covid-19. ABSTRACT This study aims to determine what factors influence the decisions of Islamic stock investors in Surabaya during the Covid-19 pandemic. These factors are obtained through market variables, financial literacy, herding behavior, and risk tolerance. The research method uses a quantitative approach with analytical techniques, namely confirmatory factor analysis. This study used purposive and snowball sampling to get 100 respondents through questionnaires distributed according to the predetermined criteria. The results found that three factors influence the decisions of Islamic stock investors in Surabaya during the Covid-19 pandemic, i.e., herding behavior as the main factor, investment knowledge as the second factor, and market variables as the third factor. Keywords: Herding Behavior, Investment Knowledge, Market Variables, Investment Decisions, Covid-19 Pandemic. DAFTAR PUSTAKA Ahmed, Z., & Noreen, U. (2021). Role of behavioral determinants for investment decision making. Asia-Pacific Social Science Review, 21(2), 48-62. Al-Tamimi, H., & Kalli, A. A. B. (2009). Financial literacy and investment decisions of UAE investors. Journal of Risk Finance, 10(5), 500–516. https://doi.org/10.1108/15265940911001402 Anita, I., Tampubolon, J. N., & Rachman, A. A. (2021). Factors affecting the investment decision on stock investors during pandemic covid-19. Turkish Journal of Physiotherapy and Rehabilitation, 32(2), 3884–3899. https://turkjphysiotherrehabil.org/pub/pdf/322/32-2-504.pdf Asiedu, E., Jin, Y., & Kanyama, I. K. (2015). The impact of HIV/AIDS on foreign direct investment: Evidence from Sub-Saharan Africa. Journal of African Trade, 2(1–2), 1-17. https://doi.org/10.1016/j.joat.2015.01.001 Bachrudin, A., & Tobing, H. L. (2003). Analisis data untuk penelitian survey. Bogor: In Media. Bappenas. (2020). Laporan perkembangan ekonomi Indonesia dan dunia triwulan III tahun 2020. Jakarta: Kementerian PPN/Bappenas. BEI. (2021). Database galeri investasi BEI per Maret 2021. Jakarta: BEI. Ceylan, R. F., & Ozkan, B. (2020). The economic effects of epidemics: from SARS and MERS to COVID-19. Research Journal in Advanced Humanities, 1(2), 21–29. https://royalliteglobal.com/advanced-humanities/article/view/132 Chavas, J.-P. (2004). Risk analysis in theory and practice. USA: Elsevier Academic Press. Chen, H., & Volpe, R. P. (1998). An analysis of personal financial literacy among college students. Financial Services Review, 7(2), 107–128. https://doi.org/https://doi.org/10.1016/S1057-0810(99)80006-7 Darmawan, T., Nurwahidin., & Anwar, S. (2019). Analisis faktor-faktor yang memengaruhi keputusan investasi di pasar modal syariah. Jurnal Middle East and Islamic Studies, 6(2), 192-214. https://doi.org/10.7454/meis.v6i2.103 DelaCruz, J. (2007). A brief contribution to the debate over the impact if HIV/AIDS on economic growth. Munich Personal RePEc Archive, 2116, 0–33. Dixon, S., McDonald, S., & Roberts, J. (2002). The impact of HIV and AIDS on Africa’s economic development. British Medical Journal, 324(7331), 232–234. https://doi.org/10.1136/bmj.324.7331.232 Economou, F., Hassapis, C., & Philippas, N. (2018). Investors’ fear and herding in the stock market. Applied Economics, 50(34–35), 3654–3663. https://doi.org/10.1080/00036846.2018.1436145 Economou, F., Kostakis, A., & Philippas, N. (2011). Cross-country effects in herding behaviour: Evidence from four south European markets. Journal of International Financial Markets, Institutions and Money, 21(3), 443–460. https://doi.org/10.1016/j.intfin.2011.01.005 Fridana, I. O., & Asandimitra, N. (2020). Analisis faktor yang memengaruhi keputusan investasi (studi pada mahasiswi di surabaya). Jurnal Muara Ilmu Ekonomi dan Bisnis, 4(2), 396. https://doi.org/10.24912/jmieb.v4i2.8729 Ghalandari, K., & Ghahremanpour, J. (2013). The effect of market variables and herding effect on investment decision as factor influencing investment performance in Iran. Journal of Basic and Applied Scientific Research, 3(3), 313–318. Ghozali, I. (2001). Aplikasi analisis multivariate dengan program SPSS. Semarang: Badan Penerbit UNDIP. Ghozali, I. (2005). Aplikasi analisis multivariate dengan program SPSS. Semarang: Badan Penerbit UNDIP. Grable, J., & Lytton, R. (1999). Financial risk tolerance revisited: The development of a risk assessment instrument. Financial Services Review, 8(3), 163–181. https://doi.org/10.1016/s1057-0810(99)00041-4 Hadrian, H., & Adiputra, I. G. (2020). Pengaruh overconfidence, herding effect, self-monitoring terhadap investment decision pada masa pandemi covid-19. Jurnal Manajerial dan Kewirausahaan, 2(3), 595. https://doi.org/10.24912/jmk.v2i3.9571 Hair, F. J., Black, C. W., Babin, B. J., & Anderson, R. (2010). Multivariate Data Analysis. UK: Pearson Education. Hendarto, K., Anastasia, N., & Basana, S. R. (2021). The effect of financial literacy, financial risk tolerance, and financial socialization agents on stock investment decision in the millennial generation. Petra International Journal of Business Studies, 4(1), 11–22. https://doi.org/10.9744/ijbs.4.1.11-22 Hung, A., Parker, A. M., & Yoong, J. (2011). Defining and measuring financial literacy. SSRN Electronic Journal. https://doi.org/10.2139/ssrn.1498674 Inayah, N. I. (2020). Prinsip-prinsip ekonomi Islam dalam investasi syariah. Aksy: Jurnal Ilmu Akuntansi dan Bisnis Syariah, 2(2), 89-100. https://doi.org/10.15575/aksy.v2i2.9801 Jannah, W., & Ady, S. U. (2017). Analisis fundamental, suku bunga, dan overconfidence terhadap pengambilan keputusan investasi pada investor di Surabaya. Ekspektra: Jurnal Bisnis dan Manajemen, 1(2), 138-155. https://doi.org/10.25139/ekt.v0i0.338 Keller, C., & Siegrist, M. (2006). Investing in stocks: The influence of financial risk attitude and values-related money and stock market attitudes. Journal of Economic Psychology, 27(2), 285–303. https://doi.org/https://doi.org/10.1016/j.joep.2005.07.002 Kemenkes RI. (2020). Pertanyaan dan jawaban terkait coronavirus disease 2019 (covid-19). World Health Organization, 2019, 1–13. https://www.who.int/indonesia/news/novel-coronavirus/qa-for-public Kiev, A. (2003). The psychology of risk: Mastering market uncertainty. USA: John Wiley & Sons, Inc. Lakonishok, J., Shleifer, A., & Vishny, R. W. (1992). The impact of institutional trading on stock prices. Journal of Financial Economics, 32(1), 23–43. https://doi.org/10.1016/0304-405X(92)90023-Q Lee, J. (2004). Globalization and disease : The case of SARS. Asian Economic Papers, 3(1), 113-131. http://dx.doi.org/10.1162/1535351041747932 Luong & Ha. (2011). Behavioral factors influencing individual investors´ decision-making and performance: A survey at the Ho Chi Minh Stock Exchange. Unpublished master thesis. Sweden: Umea University. Mahmood, Z., Kouser, R., Abbas, S. S., & Saba, I. (2016). The effect of hueristics, prospect and herding factors on investment performance. Pakistan Journal of Social Sciences (PJSS), 36(1), 475–484. http://www.bzu.edu.pk/PJSS/Vol36No12016/PJSS-Vol36-No1-42.pdf OJK. (2019). Survei nasional literasi dan inklusi keuangan Indonesia 2019. Jakarta: OJK. OJK. (2020). Statistik November - minggu 3. Retrieved from https://ojk.go.id/id/kanal/pasar-modal/data-dan-statistik/statistik-pasar-modal/Pages/november-minggu-3.aspx Pak, O., & Mahmood, M. (2015). Impact of personality on risk tolerance and investment decisions: A study on potential investors of Kazakhstan. International Journal of Commerce and Management, 25(4), 370–384. https://doi.org/10.1108/IJCoMA-01-2013-0002 Pepinsky, T. B., & Wihardja, M. M. (2011). Decentralization and economic performance in Indonesia. Journal of East Asian Studies, 11(3), 337–371. https://doi.org/10.1017/S1598240800007372 Putri, R. A., & Isbanah, Y. (2020). Faktor-faktor yang memengaruhi keputusan investasi pada investor saham di Surabaya. Jurnal Ilmu Manajemen, 8(1), 197–209. Ramdani, N. F. (2018). Analisis pengaruh representativeness bias dan herding behavior terhadap keputusan investasi (Studi pada mahasiswa di Yogyakarta). DSpace Universitas Islam Indonesia, 1–16. Rivo, M. C., & Ratnasari, R. T. (2020). Faktor yang mempengaruhi perilaku investor muslim dalam keputusan berinvestasi saham syariah. Jurnal Ekonomi Syariah Teori dan Terapan, 7(11), 2202-2220. https://doi.org/10.20473/vol7iss202011pp2202-2220 Salvatore, T., & Esra, M. A. (2020). Pengaruh overconfidence, herding, regret aversion, dan risk tolerance terhadap pengambilan keputusan investasi investor. Jurnal Manajemen, 10(1), 48–56. https://doi.org/10.46806/jm.v10i1.699 Saputro, R. E. H., & Lestari, D. (2019). Effect of financial literacy and risk perception on student investment decisions in Jakarta. Review of Management and Entrepreneurship, 3(2), 107–132. https://doi.org/10.37715/rme.v3i2.1237 Sitkin, S. B., & Pablo, A. L. (1992). Reconceptualizing the determinants of risk behavior. Academy of Management Review, 17(1), 9–38. https://doi.org/10.5465/amr.1992.4279564 TradingView.com. (2020). Indeks harga saham gabungan 2020. Retrieved from https://id.tradingview.com/ Ullah, S. (2015). An empirical study of illusion of control and self-serving attribution bias, impact on investor’s decision making: Moderating role of financial literacy. Research Journal of Finance and Accounting, 6(19), 109–118. Van Rooij, M., Lusardi, A., & Alessie, R. (2011). Financial literacy and stock market participation. Journal of Financial Economics, 101(2), 449–472. https://doi.org/10.1016/j.jfineco.2011.03.006 Virlics, A. (2013). Investment decision making and risk. Procedia Economics and Finance, 6(13), 169–177. https://doi.org/10.1016/s2212-5671(13)00129-9 Vitt, L. a., Kent, J., Lyter, D. M., Siegenthaler, J. K., & Ward, J. (2000). Personal finance and the rush to competence: Financial literacy education in the U.S. Personal Finance, October, 1–234. www.isfs.org/documents-pdfs/rep-finliteracy.pdf Waweru, N. M., Munyoki, E., & Uliana, E. (2008). The effects of behavioural factors in investment decision-making: a survey of institutional investors operating at the Nairobi Stock Exchange. International Journal of Business and Emerging Markets, 1(1), 24–41. https://dx.doi.org/10.1504/IJBEM.2008.019243 WHO. (2020). Weekly epidemiological update - 27 December 2020. Genève, Switzerland, December, 17. Retrieved from https://www.who.int/publications/m/item/weekly-epidemiological-update—29-december-2020 Wong, M. C. S., & Cheung, Y. L. (1999). The practice of investment management in Hong Kong: Market forecasting and stock selection. Omega, 27(4), 451–465. https://doi.org/10.1016/S0305-0483(98)00070-X Zulfiqar, M., & Bilal, M. (2016). Financial wellbeing is the goal of financial literacy. Research Journal of Finance and Accounting, 7(11), 94–103. https://jurnaljam.ub.ac.id/index.php/jam/article/view/1721